CO2 conversion to phenyl isocyanates by uranium(vi) bis(imido) complexes. Issue 3 (11th December 2019) - Maria, Leonor; Bandeira, Nuno A. G.; Marçalo, Joaquim; Santos, Isabel C.; Gibson, John K.
Abstract : U(vi ) trans -bis(imido) complexes [U(κ 4 {( t Bu2 ArO)2 Me2 -cyclam})(NPh)(NPh R )] react with CO2 to afford U(vi ) trans -[OUNR] 2+ complexes with elimination of isocyanates. These are unprecedented examples of CO2 cleavage mediated by U(vi ) imido complexes. Abstract : Uranium(vi ) trans -bis(imido) complexes [U(κ 4 -{( t Bu2 ArO)2 Me2 -cyclam})(NPh)(NPh R )] react with CO2 to eliminate phenyl isocyanates and afford uranium(vi ) trans -[OUNR] 2+ complexes, including [U(κ 4 -{( t Bu2 ArO)2 Me2 -cyclam})(NPh)(O)] that was crystallographically characterized. DFT studies indicate that the reaction proceeds by endergonic formation of a cycloaddition intermediate; the secondary reaction to form a dioxo uranyl complex is both thermodynamically and kinetically hindered.